2019
DOI: 10.12688/wellcomeopenres.14867.2
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and host species-specific transcriptional changes in models of experimental visceral leishmaniasis

Abstract: Background: Human visceral leishmaniasis, caused by infection with Leishmania donovani or L. infantum, is a potentially fatal disease affecting 50,000-90,000 people yearly in 75 disease endemic countries, with more than 20,000 deaths reported. Experimental models of infection play a major role in understanding parasite biology, host-pathogen interaction, disease pathogenesis, and parasite transmission. In addition, they have an essential role in the identification and pre-clinical evaluation of new drugs and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 81 publications
2
31
1
Order By: Relevance
“…Given the many studies that have identified the importance of regulatory IL-10 in VL pathogenesis [54, 5659], it was of some interest in our study that IL10 was not identified as a top differentially expressed gene or as a significantly enriched signalling pathway in either comparison of active cases with healthy controls, or of active cases with treated cases. Nor did we observed perturbation of IL10R as has been reported in experimental transcriptional profiling studies of VL [24]. Indeed, downregulated expression of the type 2 cytokine gene IL4 was the strongest response associated with effective cure in liposome-encapsulated amphotericin B treated cases, in line with previous studies showing that IL-4 levels were two-fold higher in VL patients who had failed treatment compared to previously untreated patients, whereas IL-10 levels were comparable in both [58].…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Given the many studies that have identified the importance of regulatory IL-10 in VL pathogenesis [54, 5659], it was of some interest in our study that IL10 was not identified as a top differentially expressed gene or as a significantly enriched signalling pathway in either comparison of active cases with healthy controls, or of active cases with treated cases. Nor did we observed perturbation of IL10R as has been reported in experimental transcriptional profiling studies of VL [24]. Indeed, downregulated expression of the type 2 cytokine gene IL4 was the strongest response associated with effective cure in liposome-encapsulated amphotericin B treated cases, in line with previous studies showing that IL-4 levels were two-fold higher in VL patients who had failed treatment compared to previously untreated patients, whereas IL-10 levels were comparable in both [58].…”
Section: Discussionmentioning
confidence: 61%
“…Cxcl9, Gbp1 (encoding the interferon-γ-induced guanylate binding protein GBP1 identified here as one of the top 10 induced genes when comparing active versus treated cases), and Ifng were also identified as part of a common signature of 26 genes upregulated in blood, spleen and liver throughout the course of experimental infection with L . donovani in susceptible BALB/c mice, with Cxcl9 and Gbp1 reported as hub genes from a STRING analysis [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human VL, comparisons between the whole blood transcriptome of healthy endemic controls with active cases, drug-cured cases and asymptomatic individuals have been reported from Brazil [45] and India [46]. Transcriptomic analysis of the splenic, hepatic and blood response to infection over time has been performed in mice [47] and for spleen only in hamsters [48]. High level analysis of these various reports indicates (i) IFN signatures are a prominent feature of infection; (ii) Th2 responses are variably represented with a bias to more severe disease; iii) changes associated with cell cycle, lipid metabolism, angiogensis and hematological disturbances are evident in active disease and reduced after treatment; iv) treated patients, at least over the time period of study, fail to fully return to a homeostatic state.…”
Section: Systemic Changes In Metabolic and Immune Pathwaysmentioning
confidence: 99%
“…Instead, most studies rely on the detection of immune signatures in peripheral blood to evaluate the performance of vaccine candidates 5,6 , or to identify markers of protective immunity or pathology in humans 79 . Despite this obvious discrepancy and mounting evidence of tissue-specific differences in gene expression during immune responses 10,11 , there has not been a comprehensive analysis of simultaneous measurements from blood and spleen over the course of a Plasmodium infection to evaluate how similar or dissimilar the immune signatures in these two tissues are.…”
Section: Introductionmentioning
confidence: 99%